2001
DOI: 10.21273/horttech.11.4.603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Low-rate Herbicides to Supplement Methyl Bromide Alternative Fumigants to Control Weeds in Strawberry

Abstract: Methyl bromide has been the foundation of chemical weed control in strawberry (Fragaria ×ananassa) in California for over 40 years. The impending phaseout of methyl bromide may leave strawberry producers dependent on less efficacious alternative fumigants for weed control. The use of herbicides to supplement fumigants is a potential weed control strategy for strawberry. A 2-year field study was conducted in California to evaluate 10 herbicides as po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…A 2010 survey by the Southern Weed Science Society reported that purple and yellow nutsedges are the most common and troublesome weeds in fruiting vegetable crops in Florida (Webster 2010). There are very few POST herbicides that are safe to use on strawberries (Manning and Fennimore 2001), and in Florida, clopyralid, clethodim, and sethoxydim are the only POST herbicides registered (Anonymous 2015; Figueroa and Doohan 2006; Vallad et al 2014). Currently, there are no herbicides with activity on nutsedge registered for use in strawberry.…”
mentioning
confidence: 99%
“…A 2010 survey by the Southern Weed Science Society reported that purple and yellow nutsedges are the most common and troublesome weeds in fruiting vegetable crops in Florida (Webster 2010). There are very few POST herbicides that are safe to use on strawberries (Manning and Fennimore 2001), and in Florida, clopyralid, clethodim, and sethoxydim are the only POST herbicides registered (Anonymous 2015; Figueroa and Doohan 2006; Vallad et al 2014). Currently, there are no herbicides with activity on nutsedge registered for use in strawberry.…”
mentioning
confidence: 99%
“…An economic analysis conducted by the U.S. Department of Agriculture indicates that the phaseout of MeBr as a preplant soil fumigant may have substantial impact on many commodities because no known single alternative fumigant, chemical, or other technology exists that can readily substitute for MeBr in efficacy, cost, ease of use, availability, worker safety, and environmental safety below the ozone layer (Osteen, 2003;USDA, 2008a). Among possible alternatives are host plant resistance, biological control, cultural practices, and alternative chemicals, either alone or in combination (Gullino et al, 2003;Manning and Fennimore, 2001;Martin, 2003;Rieger et al, 2001;Ristaino and Thomas, 1997;Rosskopf et al, 2005;Schneider et al, 2003). A few products that have a long history of use include 1,3-dichloropropene, metam sodium, chloropicrin, and combinations of these [e.g., 61.1% 1,3-dichloropropene + 34.7% chloropicrin (Telone-C35 TM ; Dow Agro-Sciences, Indianapolis)] (Duniway, 2002;Martin, 2003;Schneider et al, 2003).…”
mentioning
confidence: 99%
“…Crop tolerance was evaluated 1 and 3 WAA by visually estimating the percent plant stunting and chlorosis, where 0 = no visible damage and 100 = death of strawberry plants. Six WAA stolons were counted from the fi ve central plants in each plot and the diameter of the crop canopy was measured as described by Manning and Fennimore (2001). At 18 WAA crop tolerance was reassessed, by measuring plant height and percent of ground covered by the strawberry canopy.…”
Section: Herbicide Efficacy Studiesmentioning
confidence: 99%